DNA methylation alterations—potential cause of endometriosis pathogenesis or a reflection of tissue heterogeneity? - Saare, M; Krigul, KL; Laisk-Podar, T; Ponandai-Srinivasan, S; Rahmioglu, N; Kumar, PG; Zondervan, K; Salumets, A; Peters, M (Oxford University Press, 2018)
Alterations in the DNA methylation pattern of endometriotic lesions and endometrium of endometriosis patients have been proposed as one potential factor accompanying the endometriosis development. Although many differentially methylated genes have been associated with the pathogenesis of this disease, the overlap between the results of different studies has remained small. Among other potential confounders, the impact of tissue heterogeneity on the outcome of DNA methylation studies should be considered, as tissues are mixtures of different cell types with their own specific DNA methylation signatures. This review focuses on the results of DNA methylation studies in endometriosis from the cellular heterogeneity perspective. We consider both the studies using highly heterogeneous whole-lesion biopsies and endometrial tissue, as well as pure cell fractions isolated from lesions and endometrium to understand the potential impact of the cellular composition to the results of endometriosis DNA methylation studies. Also, future perspectives on how to diminish the impact of tissue heterogeneity in similar studies are provided.